Increased risk of dementia in patients hospitalized with acute kidney injury: A nationwide population-based cohort study. - Hsin-Hsi Tsai (PLoS ONE, 2017)
PURPOSE:To determine whether acute kidney injury (AKI) is a risk factor for dementia. METHODS:This nationwide population-based cohort study was based on data from the Taiwan National Health Insurance Research Database for 2000-2011. The incidence and relative risk of dementia were assessed in 207788 patients hospitalized for AKI. The comparison control was selected using the propensity score based on age, sex, index year and comorbidities. RESULTS:During the 12-year follow-up, patients with AKI had a significantly higher incidence for developing dementia than did the controls (8.84 vs 5.75 per 1000 person-y). A 1.88-fold increased risk of dementia (95% confidence interval, 1.76-2.01) was observed after adjustment for age, sex, and several comorbidities (diabetes, hypertension, hyperlipidemia, head injury, depression, stroke, chronic obstructive pulmonary disease, coronary artery disease, congestive heart failure, atrial fibrillation, cancer, liver disease, chronic infection/inflammation, autoimmune disease, malnutrition). CONCLUSIONS:We found that patients with AKI exhibited a significantly increased risk of developing dementia. This study provides evidence on the association between AKI and long-term adverse outcomes. Additional clinical studies investigating the related pathways are warranted.